Decellularized skeletal muscle: A versatile biomaterial in tissue engineering and regenerative medicine. (April 2022) - Philips, Charlot; Terrie, Lisanne; Thorrez, Lieven
Abstract: A wide range of synthetic and natural biomaterials is available for skeletal muscle tissue engineering. One class of natural biomaterials consists of the extracellular matrix (ECM) from donor skeletal muscle. To obtain this ECM, the cellular compartment must be completely removed while retaining the native composition and ultrastructure of the tissue as much as possible. In this review, the progress and challenges in the field of skeletal muscle decellularization are discussed by reviewing the different decellularization methods available and by highlighting the different applications of the scaffolds. Decellularized skeletal muscle has mainly been studied in the context of regeneration with a focus on its tissue-specific morphological features as well as biochemical cues to stimulate muscle regeneration. However, in this review, the potential applications of decellularized skeletal muscle are expanded beyond the regenerative setting to demonstrate its versatility as a biomaterial. Acellular matrices are discussed as a platform to study cell-matrix interactions and drug screening. Decellularized skeletal muscle ECM can also be further processed to re-engineer its structure. An overview is presented of materials processed from decellularized skeletal muscle, ranging from injectable hydrogels, bioinks for 3D bioprinting, electrospun nanofibers to coatings for cell culture.